2013
DOI: 10.1007/s13142-013-0194-3
|View full text |Cite
|
Sign up to set email alerts
|

A staff training and management intervention in VA long-term care: impact on feeding assistance care quality

Abstract: Efforts to translate efficacious interventions into longterm care practice have had limited success due to the lack of consideration of key translational intervention components. A multi-faceted intervention was implemented in two veteran affairs facilities to improve feeding assistance care. There were three study phases: baseline, intervention, and follow-up. During each phase, trained research staff conducted standardized observations of 12 meals/participant to assess feeding assistance care quality. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(92 reference statements)
1
13
0
Order By: Relevance
“…However, social interactions between routine staff and residents only occurred about half of the time during meals in the intervention group and although significantly (P < 0.05) different, was only a small increase from baseline (89). The second study, which attempted to transfer skills and knowledge to staff, was less successful than the first where the researchers were the interventionists (89). Both studies had a small amount of attrition; the first study had 24 of 148 dropout (63), and the second study had 17 of 147 dropout (89).…”
Section: Eating Assistance Trainingmentioning
confidence: 81%
See 4 more Smart Citations
“…However, social interactions between routine staff and residents only occurred about half of the time during meals in the intervention group and although significantly (P < 0.05) different, was only a small increase from baseline (89). The second study, which attempted to transfer skills and knowledge to staff, was less successful than the first where the researchers were the interventionists (89). Both studies had a small amount of attrition; the first study had 24 of 148 dropout (63), and the second study had 17 of 147 dropout (89).…”
Section: Eating Assistance Trainingmentioning
confidence: 81%
“…The crossover demonstrated that benefits continued after the intervention (63). However, social interactions between routine staff and residents only occurred about half of the time during meals in the intervention group and although significantly (P < 0.05) different, was only a small increase from baseline (89). The second study, which attempted to transfer skills and knowledge to staff, was less successful than the first where the researchers were the interventionists (89).…”
Section: Eating Assistance Trainingmentioning
confidence: 84%
See 3 more Smart Citations